The Effect Of Dietary Interventions On Arterial Stiffness In Men. A Systematic Review Of The Literature (The Review of Diabetic Studies, 2024)
Background and introductionCardiovascular diseases (CVDs) are the leading cause of death globally, encompassing conditions like coronary heart disease and strokes. Risk factors include hypertension, diabetes, and lifestyle choices such as smoking. Arterial stiffness is a crucial risk factor in hypertension, refers to the reduced flexibility of the arterial walls. This condition arises as blood vessels age and is associated with various cardiovascular diseases. Studies have shown that dietary interventions can significantly reduce CVD risks by improving factors like blood pressure and arterial stiffness, particularly in men. This paper is to systematically review the current literature on the effects of different dietary interventions on arterial stiffness in menMethodology This systematic review adheres to PRISMA guidelines, employing a flow diagram to outline the article selection process, focusing on adult males at risk for cardiovascular diseases. It assesses the impact of dietary interventions on arterial stiffness, measured by carotid-femoral pulse wave velocity (PWV). The review specifically includes randomized controlled trials (RCTs) published from January 2015 to June 2024 that are in English and utilize PWV for measuring arterial stiffness. Excluded are non-RCT studies, those combining diet with exercise, and those involving females, children, or mixed groups. Primary outcomes are changes in PWV, while secondary outcomes include variations in systolic blood pressure, heart rate, and triglycerides.Results The systematic review process identified five randomized controlled trials (RCTs) met the inclusion criteria out of an initial 1,131 papers after rigorous screening. Only one study using cocoa flavanol intervention achieved significant reduction on the pulse wave velocity, the same study also showed significant decrease in systolic blood pressure, also another study showed significant reduction in systolic blood pressure after consumption of high fat beef patties.Conclusion This review indicated that cocoa flavanols can significantly improve arterial stiffness and systolic blood pressure, but other dietary interventions lacked similar impactful results. The findings suggest that effective strategies might need to integrate diet with exercise and other lifestyle changes to significantly enhance cardiovascular health.